2020
DOI: 10.3390/insects11020110
|View full text |Cite
|
Sign up to set email alerts
|

Species Composition, Temporal Abundance and Distribution of Insect Captures Inside and Outside Commercial Peanut Shelling Facilities

Abstract: Insect populations were studied within two commercial peanut shelling facilities located in the southeastern United States. Commercially available pheromone/kairomone-baited dome traps and pheromone-baited flight traps were deployed throughout processing and shipping portions of the shelling plants and serviced weekly over one year. Lasioderma serricorne, Tribolium castaneum, Typhaea stercorea, Carpophilus spp., Plodia interpunctella and Cadra cautella were the most common captures across locations. Lasioderma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Thus, Warehouse 2 had much lower relative abundance of L. serricorne than Warehouse 1. Lasioderma serricorne was also found co-occur with P. interpunctella in a botanicals warehouse and peanut shelling facility (Arbogast et al 2002, Abdelghany et al 2010, Perez et al 2020). Lasioderma serricorne activity exhibited a seasonal pattern and the population size remained stable in both warehouses during the study period except for a large increase during weeks 40–42 (October) in 2020.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, Warehouse 2 had much lower relative abundance of L. serricorne than Warehouse 1. Lasioderma serricorne was also found co-occur with P. interpunctella in a botanicals warehouse and peanut shelling facility (Arbogast et al 2002, Abdelghany et al 2010, Perez et al 2020). Lasioderma serricorne activity exhibited a seasonal pattern and the population size remained stable in both warehouses during the study period except for a large increase during weeks 40–42 (October) in 2020.…”
Section: Discussionmentioning
confidence: 97%
“…Perez et al reported on population dynamics and the temporal abundance of postharvest pests on peanuts within two commercial shelling facilities located in the southeastern United States [2]. In order to institute an effective pest management program in any postharvest system, active pest monitoring, the correct identification of pests, and shifts in pest populations with temperature and time have to be understood [7].…”
Section: Population Dynamics and Trapping Of Postharvest Pests In Peanutsmentioning
confidence: 99%
“…More insects were found in the processing areas of the plants, and increased temperature was highly correlated with increased pest populations in the plants. The study concluded that pest management efforts should be concentrated at the entrance point for in-shell peanuts into the plants [2].…”
Section: Population Dynamics and Trapping Of Postharvest Pests In Peanutsmentioning
confidence: 99%
See 1 more Smart Citation